Sport tourism quality and its influence on visitor satisfaction and revisit intention: an empirical study of Mandalika MotoGP - Clarens Anthony Chandra; Troy Iversen Jaya Kusuma; Serli Wijaya (Universitas Merdeka Malang, 2023)
Sport tourism has been proven as a special interest tourism that contributes positively to the economy and the destination image of the event’s host. MotoGP is an international motorcycle racing championship in the premier class of the Grand Prix motorcycle racing series. This study aims to measure the influence of visitor perceptions on the quality of sport tourism from the Mandalika MotoGP event on satisfaction and intention to visit and attend the same event again in subsequent years. The online survey was distributed to 200 respondents who attended the Mandalika MotoGP in 2022 and stayed at one of the accommodation facilities around the area during the event. This study uses SEM-PLS for primary data processing. The results of the study show that perceptions of the quality of sport tourism have a positive effect on the level of satisfaction which then also encourages tourists to return to the same event in the future. In relation to the four dimensions that determine the quality of sport tourism, contest quality and venue quality are two dimensions that most contribute to shaping tourist satisfaction.